Angelica acutiloba Kitagawa Extract Attenuates DSS-Induced Murine Colitis - Jong-Chan Jang; Kang Min Lee; Seong-Gyu Ko (Mediators of Inflammation)
We examined the protective effects of Angelica acutiloba Kitagawa (AAK) extract on a murine model of acute experimental colitis. Colitis was induced by 4% dextran sulfate sodium (DSS) in the drinking water of male C57BL/6 mice, for 7 consecutive days. Oral administration of AAK extract (500 mg/kg/day) significantly alleviated DSS-induced symptoms such as anorexia, weight loss, events of diarrhea or bloody stools, and colon shortening. Histological damage was also ameliorated, as evidenced by the architectural preservation and suppression of inflammatory cell infiltration in colonic samples. Treatment improved the colonic mRNA expression of different inflammatory markers: cytokines, inducible enzymes, matrix metalloproteinases, and tight junction-related proteins. In the isolated serum, IgE levels were downregulated. Collectively, these findings indicate the therapeutic potentials of AAK as an effective complementary or alternative modality for the treatment of ulcerative colitis.